TSPO deficiency induces mitochondrial dysfunction, leading to hypoxia, angiogenesis, and a growth-promoting metabolic shift toward glycolysis in glioblastoma. Issue 2 (24th September 2019) - Fu, Yi; Wang, Dongdong; Wang, Huaishan; Cai, Menghua; Li, Chao; Zhang, Xue; Chen, Hui; Hu, Yu; Zhang, Xuan; Ying, Mingyao; He, Wei; Zhang, Jianmin
Abstract: Background: The ligands of mitochondrial translocator protein (TSPO) have been widely used as diagnostic biomarkers for glioma. However, the true biological actions of TSPO in vivo and its role in glioma tumorigenesis remain elusive. Methods: TSPO knockout xenograft and spontaneous mouse glioma models were employed to assess the roles of TSPO in the pathogenesis of glioma. A Seahorse Extracellular Flux Analyzer was used to evaluate mitochondrial oxidative phosphorylation and glycolysis in TSPO knockout and wild-type glioma cells. Results: TSPO deficiency promoted glioma cell proliferation in vitro in mouse GL261 cells and patient-derived stem cell–like GBM1B cells. TSPO knockout increased glioma growth and angiogenesis in intracranial xenografts and a mouse spontaneous glioma model. Loss of TSPO resulted in a greater number of fragmented mitochondria, increased glucose uptake and lactic acid conversion, decreased oxidative phosphorylation, and increased glycolysis. Conclusion: TSPO serves as a key regulator of glioma growth and malignancy by controlling the metabolic balance between mitochondrial oxidative phosphorylation and glycolysis. 1. TSPO deficiency promotes glioma growth and angiogenesis. 2. TSPO regulates the balance between mitochondrial oxidative phosphorylation and glycolysis.